Pesticide residues in sediments and aquatic species in Lake Nokoué and Cotonou Lagoon in the Republic of Bénin - YEHOUENOU AZEHOUN PAZOU, ELISABETH; AZEHOUN, Judicael (My University, 2013)
Lake Nokoué and Cotonou Lagoon are the most important and most productive continental freshwaters in Bénin, with an estimated fish production of over 2 tonnes per hectare in Lake Nokoué. Organochlorine pesticides are used in agriculture and to repel tsetse flies, malaria mosquitoes and other diseases raised. Sediment, fish, shrimp and oyster species were collected in Lake Nokoué and Cotonou Lagoon for pesticide residues analysis. The main pesticides identified in sediment were pp′-DDT and its metabolites pp-DDE and pp′- DDD, with residue levels between the detection limit and 24.4 μg/kg dry weight. Fish species commonly consumed such as Elops lacerta, Podamasys jubelini, Gobbienellus occidentalis, Ethmalosa fimbriata, Mugil cephalus and Hemichromis fasciatus were contaminated with residues of seven to nine pesticides, including pp- DDE, op′-DDD, pp′-DDD, op′-DDT, pp′-DDT, α-endosulfan, aldrin, dieldrin and γ-hexachlorocyclohexane. The levels ranged from detection limit to 289 ng/g lipid. The same pesticides were also detected in other aquatic species, such as shrimp and oysters. A summed risk assessment, comparing pesticide intake levels through fish consumption with tolerable daily intake levels proposed by the World Health Organization, showed in all cases a low risk for human health.
Keywords: Pesticide residues . Sediment . Fish . Oysters .; Shrimp . Human health risk